2015
DOI: 10.1002/chem.201500870
|View full text |Cite
|
Sign up to set email alerts
|

Heterolysis of Dihydrogen by Silver Alkoxides and Fluorides

Abstract: Alkoxide-bridged disilver cations react with dihydrogen to form hydride-bridged cations, releasing free alcohol. Hydrogenolysis of neutral silver fluorides affords hydride-bridged disilver cations as their bifluoride salts. These reactions proceed most efficiently when the supporting ligands are expanded N-heterocyclic carbenes (NHCs) derived from 6- and 7-membered cyclic amidinium salts. Kinetics studies show that silver fluoride hydrogenolysis is first-order in both silver and dihydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 115 publications
2
13
0
Order By: Relevance
“…Thus, the reaction follows a second‐order rate law overall such that −d[ 2‐OH ]/d t = k [ 2‐OH ][H 2 ]. This rate expression is similar to that observed for hydrogenolysis of the mononuclear ( t Bu PCP)Pd−OH and dinuclear Ag 2 (μ‐pentoxide) complexes …”
Section: Resultssupporting
confidence: 83%
“…Thus, the reaction follows a second‐order rate law overall such that −d[ 2‐OH ]/d t = k [ 2‐OH ][H 2 ]. This rate expression is similar to that observed for hydrogenolysis of the mononuclear ( t Bu PCP)Pd−OH and dinuclear Ag 2 (μ‐pentoxide) complexes …”
Section: Resultssupporting
confidence: 83%
“…Expanded-ring NHCs, derived from six- and seven-membered cyclic amidinium salts, have been shown to increase the stability of other reactive metal species. Recently, Whittlesey et al reported that (6Mes)­copper­(I) hydride (6Mes = 1,3-bis­(2,4,6-trimethylphenyl)-3,4,5,6-tetrahydropyrimidin-2-ylidene) proved too unstable to isolate but could be trapped efficiently with alkynes or ketones . We now report the synthesis of [(6Dipp)­CuH] 2 ( 3a ) and [(7Dipp)­CuH] 2 ( 3b ) (6Dipp = 1,3-bis­(2,6-diisopropylphenyl)-3,4,5,6-tetrahydropyrimidin-2-ylidene; 7Dipp =1,3-bis­(2,6-diisopropylphenyl)-4,5,6,7-tetrahydro-1,3-diazepin-2-ylidene).…”
mentioning
confidence: 78%
“…If electronic effects of the NHC ligands were the dominant factor controlling the insertion rates with CF3CO2Et, then [6CuH]2 would be expected to insert more quickly since saturated expanded-ring NHCs are more electron-donating than unsaturated imidazolylidene NHCs. [28] The stark contrast in insertion rates between [*5CuH]2 and [6CuH]2 or [7CuH]2 therefore implies steric contributions of the NHC ligands are the dominant factor. Figure 6.…”
Section: Effects Of Ligand Size Of Nhc and Electronic Properties Of Benzophenone Derivatives On The Rate Of Insertionmentioning
confidence: 99%